Pathology of Haplosporidium patagon affecting siphonariid gastropods in Patagonia - Di Giorgio, Gisele Vanesa (2014)
Haplosporidium patagon was found parasitizing Siphonaria lessonii and S. lateralis, 2 siphonariid gastropods co-occurring on the littoral rocky shore at Puerto Deseado, Santa Cruz, Argentina. Gastropods from 2 habitats representing 2 different levels of environmental harshness were studied. In both cases, S. lessonii showed a higher prevalence of infection (3.78%) over the entire 14 mo study period than S. lateralis (0.13%). Very different values of prevalence of infection were observed at the different sampling sites: Site 1, the more restrictive habitat (exposed for long periods to desiccation during low tides, higher ultraviolet exposure, and high ranges of temperature variation) showed a higher prevalence value (5.99%) than Site 2 (1.46%). Statistical differences in prevalence were also found between values corresponding to the austral spring (3.35% at Site 1 and 0.74% at Site 2) and winter (13.79% at Site 1 and 2.13% at Site 2). The presence/ absence of H. patagon did not vary significantly with gastropod shell length. Infection affected the digestive gland, whose normal histology was greatly modified. The hermaphroditic gonads were also affected; the female germinal cells disappeared or only a few primary or previtellogenic oocytes were present, and vitellogenesis was inhibited. The function of the male germinal epithelium, as well as spermatogenesis and spermiogenesis processes and associated organs (seminal vesicles and seminal receptacles), were not affected. However, the glandular pallial complex of the reproductive systemwas affected, and we observed a significant reduction in development in parasitized gastropods. H. patagon sporocysts also invaded the supporting connective tissues of both the kidney and pseudobranch.